Amino acid composition of tropical fruits and vegetables II. Bitter melon (Momordica charantia L.), eggplant (Solanum melongena L.), guava (Psidium guajava L.), mango (Mangifera indica L.), and squash (Cucurbita maxima Duch.) - Narvaez, Lilibeth Lim; De Leon, Sonia Y. (1989.)
ABSTRACT The general method of extracting amino acids from fresh fruits and vegetables such as bitter melon (Momordica charantia L.), eggplant (Solanum melongena L.), guava (Psidium guajava L.), mango (Mangifera indica L.) and squash (Cucurbita maxima Duch.) was determined through several trials. The use of 2:1 chloroform-methanol mixture was found to produce the best results, nearly 100% of the extractable amino acids. The amino acid composition of the said fruits and vegetables was also determined. From the analysis conducted, the bitter melon was found to be the most nutritious amount the other samples since it contained mostly the highest quantity of the essential amino acids. These samples were also analyzed for their proximate composition. The values obtained were found to conform with the existing literature values. Among the five tropical fruits and vegetables analyzed, the squash contained the highest concentration of glutamic acid, 12.00 mg%.
Thesis (BSFT)--University of the Philippines Diliman
Keywords: Fruits -- Philippines -- Analysis; Vegetables -- Philippines -- Analysis